Dialogic Leadership in Managing Islamic Boarding Schools for the Digital Generation - Aspandi, Ade; Nuansah, Unang; Mima, Nur Luthfiyani Fajrin; Zalil, Muhammad Abdul; Saepudin, Aep (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study explores the role of dialogic leadership in managing Islamic boarding schools and its contribution to preparing students for the challenges of the digital era. Dialogic leadership emphasizes participatory communication and shared decision-making, enabling leaders, teachers, and students to design innovative learning strategies collaboratively. The findings reveal that this leadership model increases learning efficiency by up to 30% and significantly enhances students' digital competencies, especially in using technology as a learning tool. However, key obstacles persist, including limited infrastructure and insufficient teacher readiness in adopting digital pedagogy. The study highlights the importance of aligning Islamic values — such as discipline, cooperation, and sincerity — with modern educational innovations to foster inclusive, future-oriented learning. Integrating tradition with technology not only strengthens students' religious character but also equips them with critical thinking and digital literacy skills. The practical implications suggest the need for structured technology training for teachers, curriculum reform oriented toward digital learning, and investment in adequate educational facilities. These efforts are crucial to transform Islamic boarding schools into adaptive and progressive institutions that nurture a generation competent in both religious and technological domains.was used